The psychological effects of peacekeeping service in Bosnia : a dissertation presented in fulfilment of the requirements for the degree of Doctor of Philosophy in Psychology at Massey University, Palmerston North, New Zealand - Mirfin, Kathryn Audrey (Massey University, 2004)
Increasing numbers of military and civilian personnel deploy overseas on peacekeeping duties. Although these are widely acknowledged as stressful, the psychological effects of peacekeeping duties are unclear. Results from previous research in this area are mixed, perhaps because many studies suffer from methodological limitations. This study sought to overcome some of these methodological limitations by utilising a controlled, longitudinal design. The aims of the study were to establish whether there were any changes in mental health (adverse mental health and psychological well-being) as a result of a peacekeeping deployment; to examine possible predictors where changes did occur; to assess the incidence of Post Traumatic Stress Disorder (PTSD) amongst the peacekeepers; to make comparisons with other groups to gain an understanding of the specific stressors of the peacekeeping experience and to develop a measure of the potentially traumatic stressors involved in peacekeeping service. The study examined the mental health status and the nature of the stressors experienced by a group of New Zealand Army soldiers who deployed to Bosnia at four stages of the deployment (pre-deployment, mid-deployment, post-deployment and follow-up). The mental health status of members of three control groups, New Zealand Defence Force (NZDF) personnel who deployed overseas on other than peacekeeping duties, NZ Army personnel, matched with the Experimental Group, who remained on duty in New Zealand, and a group of civilians, was examined at three of these deployment stages (pre-deployment, post-deployment and follow-up). Unfortunately the research suffered from a decline in response rate across the stages of the study, and this limited some of the analyses. Nonetheless, the robust nature of the design allowed some firm conclusions to be made. Results show that peacekeeping service can have an adverse effect on the mental health of those personnel who undertake such duties. Levels of Post Traumatic Stress Disorder (PTSD) and depression symptoms and PTSD "caseness" increased throughout the study for those soldiers who deployed to Bosnia but for none of the control groups. This suggests that these increases were specific to deploying to Bosnia, rather than deploying overseas on other than peacekeeping duties or remaining in NZ in either the NZ Army or the civilian sector. The most stressful time for those who deploy on peacekeeping missions is the follow-up (six months after return to NZ) stage, and to a lesser extent, the pre-deployment stage. A number of stressors were associated with all deployment stages, and some were unique to each deployment stage. The Peacekeeping Exposure Scale (PES) developed in the current study seems a sound measure of the potentially traumatic events involved in peacekeeping service. Experience of some types of these events along with "post-deployment" stress are the best predictors of PTSD at follow-up. Recommendations include addressing the specific stressors of each stage, in particular the follow-up and pre-deployment stages, and ensuring that support is available well after the deployment.
Keywords: United Nations Peacekeeping Forces; Soldiers; Post-traumatic stress disorder; Psychology; New Zealand Armed Forces; Bosnia; Hercegovina